Las Memorias de Gonzalo Fernández de Oviedo : Volumen I - Fernández de Oviedo y Valdes, Gonzalo, 1478-1557 (North Carolina studies in the Romance languages and literatures. Texts, textual studies, and translations, 2019)
This is an edition of the parts of the Quincuagenas of Gonzalo Fernandez de Oviedo that the author considers "aspectos de las Quincuagenas que podemos considerar respaldados por las vivencias del autor," hence the title Memorias. We are left, however, with two substantial volumes of which this is the first.